Sight, sound, motion : applied media aesthetics - Zettl, Herbert. 4 0 16; 5 (Australia : Wadsworth, Cengage Learning, 2013)
Describes the major aesthetic image elements--light and color, space, time/motion, and sound--and presents in-depth coverage of how they are creatively used in television and film.
Applied media aesthetics -- The first aesthetic field : Light -- Structuring the first aesthetic field : Lighting -- The extended first field : Color -- Structuring color : Function and composition -- The two-dimensional field : Area -- The two-dimensional field : Forces within the screen -- Structuring the two-dimensional field : Interplay of screen forces -- The three-dimensional field : Depth and volume -- Structuring the three-dimensional field : Screen volume and effects -- Building screen space : Visualization -- The four-dimensional field : Time -- The four-dimensional field : Motion -- Structuring the four-dimensional field : Timing and principal motions -- The five-dimensional field : Sound -- Structuring the five-dimensional field : Sound structures and sound/picture combinations -- Visual narrative : the syntax of continuity editing -- Visual narrative : the syntax of complexity editing.
Includes bibliographical references (p. 405-408) and index.
Keywords: 2 -- 0; 6; Production and direction.;Aesthetics. -- Cinematography.;Motion pictures;Motion pictures -- 20; 20; 2